Dual active nitrogen doped hierarchical porous hollow carbon nanospheres as an oxygen reduction electrocatalyst for zinc–air batteries. Issue 35 (30th August 2017) - Zhu, Jiawei; Zhou, Huang; Zhang, Chengtian; Zhang, Jian; Mu, Shichun
Abstract : Advanced dual active N-doped hollow carbon nanospheres possess superior ORR performance and can be applied in practical electrochemical energy devices. Abstract : Developing non-platinum catalysts for the oxygen reduction reaction (ORR) has become urgent for electrochemical energy devices. Herein, we synthesize N-doped hollow carbon nanospheres (N-HCNs) which only contain active pyridinic-N and graphitic-N by using polystyrene spheres and aniline as the corresponding template and precursor. The electrochemical measurements show that N-HCNs possess superior ORR electrocatalytic activity (half-wave potential is 15 mV higher than that of the precious Pt/C electrocatalyst), durability and anti-toxicity to Pt/C in alkaline media. Simultaneously, N-HCNs also reveal comparable ORR activity and superior stability to Pt/C in acidic media. Such high ORR performance can be ascribed to their hierarchical porous structure, ultra-high specific surface area, plenty of edge defects and high contents of active N atoms. It is noteworthy that when used as the catalyst for the air electrode of zinc–air batteries, N-HCNs present a higher power density and a larger operating voltage than Pt/C at the same discharge current density.